A single center retrospective study on real world CAR T-cell therapy: focus on early hematological toxicity - Lesan, Vadim; Christofyllakis, Konstantinos; Bewarder, Moritz; Thurner, Lorenz; Bittenbring, Jörg (Frontiers in Medicine, 2024)
Patients with relapsed/refractory diffuse large B-cell lymphoma (DLBCL), mantle cell lymphoma (MCL) and multiple myeloma have poor outcomes. CAR-T completely changed the landscape of therapy options, improving not only response rates but also survival outcomes. Hematological toxicity after chimeric antigen receptor therapy (CAR-T) is of increasing interest, being a recognized prognostic factor in this setting. We report our experience with early hematological toxicity after CAR-T therapy and point some important aspects regarding the Hematotox-Score. We identified a strong negative correlation between Hematotox-Score and platelet count at first day of cytokine release syndrome (CRS). Hematotox-Score was predictive of hemoglobin levels at day 28 after CAR-T. Ferritin remained high after 28 days post CAR-T in patients with high Hematotox-Score. Hematotox-Score did not associate with mortality in our cohort. We did not find any significant association between the hematological parameters (hemoglobin, platelets, and neutrophil counts), ferritin, LDH at first day of CRS and mortality. In conclusion, we demonstrate that Hematotox-Score is predictive of early hematological toxicity after CAR-T. Although, patients with higher degree of hematological toxicities have poorer survival outcomes, Hematotox-Score lacks predictive potential, probably due to its limitations. Further development of hematological scores predicting survival outcome in the context of CAR-T are needed.